2020
DOI: 10.1016/j.heliyon.2019.e03138
|View full text |Cite
|
Sign up to set email alerts
|

Reference urinary biopyrrin level and physiological variation in healthy young adults: relation of stress by learning

Abstract: Background: Biopyrrins are end products of oxidation reactions of bilirubin with reactive oxygen, and urinary biopyrrin (UBP) levels might increase under oxidative stress. The authors examined the reference UBP level for healthy adults and its physiological variation in 40 healthy volunteers recruited from among students of our university (20 students each from third-year and fourth-year), and compared the results with data on 8-hydroxy-2deoxyguanosine (8OHdG). Methods: UBP and 8OHdG levels could be considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…A background range for 8-OHdG has been reported in different studies for healthy persons [11,[18][19][20]. However, these studies reported a wider range of values, making the identification of background cut-off values challenging.…”
Section: Descriptive Resultsmentioning
confidence: 99%
“…A background range for 8-OHdG has been reported in different studies for healthy persons [11,[18][19][20]. However, these studies reported a wider range of values, making the identification of background cut-off values challenging.…”
Section: Descriptive Resultsmentioning
confidence: 99%
“…Hence, biopyrrins are known to be possible oxidative stress indicators. 13 The results of the current study showed that the urinary levels of 8-OHdG and biopyrrins were significantly elevated among the exposed brickfield workers when compared with their controls (Table 1). Likewise, a status of increased oxidative stress was observed in a group of Indian brick kiln workers when compared with controls.…”
Section: Discussionmentioning
confidence: 54%
“…As a result, bilirubin is now thought to be an essential in vivo ROS scavenger. Hence, biopyrrins are known to be possible oxidative stress indicators 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations